Alpha1-chimaerin, a Rac1 GTPase-activating protein, is expressed at reduced mRNA levels in the brain of Alzheimer's disease patients. (30th March 2015) - Kato, Tomoko; Konishi, Yoshihiro; Shimohama, Shun; Beach, Thomas G.; Akatsu, Hiroyasu; Tooyama, Ikuo
Highlights: Alpha1-chimaerin mRNA was localized to neurons in postmortem human brain. Reduced mRNA levels of α 1-chiamerin in the temporal cortex and hippocampus of AD. Expression of α 2-chimaerin mRNA was not reduced in the temporal cortex of AD. Abstract: Alpha1-chimaerin is a GTPase-activating protein (GAP) for Rac1, a member of the Rho small GTPase family, whose action leads to the inactivation of Rac1. Rac1 activity is upregulated in Alzheimer's disease, but little is known about the role of α 1-chimaerin. In this study, we investigated the expression and localization of α 1-chimaerin mRNA in postmortem human brains from patients with Alzheimer's disease and control subjects. In situ hybridization studies demonstrated that α 1-chimaerin was expressed by neurons in the neo-cortex of the temporal lobe and the hippocampus of both controls and Alzheimer's disease cases, with the signal intensity dramatically decreased in patients with Alzheimer's disease. Real-time PCR analysis confirmed a significant reduction of α 1-chimaerin mRNA expression in the temporal cortex of Alzheimer's disease cases. In contrast, α 2-chimaerin mRNA levels showed no significant difference between the groups. The present study showed reduced α 1-chimaerin expression in the brain of Alzheimer's disease cases, suggesting a role in the upregulation of Rac1 activity during the disease process.